Beneficial effects of Saccharomyces cerevisiae fermentation postbiotic products on calf and cow health and plausible mechanisms of action - Chae, Jeong-Byoung; Schoofs, Amy D.; McGill, Jodi L. (Frontiers in Animal Science, 2024)
Supplementation of cattle diets with Saccharomyces cerevisiae fermentation products (SCFP) has been shown to improve health and performance of calves and cows in both the dairy and feedlot. Numerous studies have shown SCFP supplementation is beneficial in the context of production- and infection-related stressors, promoting resilience, accelerated resolution of inflammation or oxidative stress, and enabling the cow or calf to maintain homeostasis. SCFPs, derived from yeast fermentation, encompass a rich array of bioactive compounds, including vitamins, minerals, amino acids, and metabolites, which likely influence the host through both distinct and overlapping processes. Understanding the mechanisms by which SCFPs exert their beneficial effects is crucial for optimizing their utilization in cattle production systems. In this review, we focused not only on the beneficial effects of SCFPs on health and performance but also on their influence on host microbiota, epithelial barrier integrity, and the host immune system, providing mechanistic insights. Previous studies have suggested that SCFPs impact host metabolism, modulate rumen and hindgut microbial populations, exert antioxidant and immunomodulatory effects, and stimulate the expression of genes involved in maintaining tissue barrier integrity. However, there are still gaps in understanding certain mechanistic pathways, particularly those involving the nervous system, as well as the paradoxical effects of SCFPs in enhancing immune responses while simultaneously mitigating excessive inflammation. This review summarizes several recent reports describing the health benefits of SCFP supplementation in cattle and considers the available evidence on the mode of action.